Intravenous Administration of Functionalized Magnetic Iron Oxide Nanoparticles Does Not Induce CNS Injury in the Rat: Influence of Spinal Cord Trauma and Cerebrolysin Treatment - Menon P.K.; Sharma A.; Lafuente J.V.; Muresanu D.F.; Aguilar Z.P.; Wang Y.A.; Patnaik R.; Mössler H.; Sharma H.S. (My University, 2025)
Influence of iron oxide magnetic nanoparticles (IOMNPs, 10 nm in diameter, 0.25 or 0.50 mg/mL in 100 μL, i.v.) on the blood–brain barrier (BBB) permeability, edema formation, and neuronal or glial changes within 4–24 h after administration was examined in normal rats and after a focal spinal cord injury (SCI). Furthermore, effect of cerebrolysin, a balanced composition of several neurotrophic factors, and active peptide fragments was also evaluated on IOMNP-induced changes in central nervous system (CNS) pathology. The SCI was inflicted in rats by making a longitudinal incision into the right dorsal horn of the T10–11 segments and allowed to survive 4 or 24 h after trauma. Cerebrolysin (2.5 mL/kg, i.v.) was given either 30 min before IOMNP injection in the 4-h SCI group or 4 h after injury in the 24-h survival groups. Control group received cerebrolysin in identical situation following IOMNP administration. In all groups, leakage of serum albumin in the CNS as a marker of BBB breakdown and activation of astrocytes using glial fibrillary acidic protein was evaluated by immunohistochemistry. The neuronal injury was examined by Nissl staining. The IOMNPs alone in either low or high doses did not induce CNS pathology either following 4 or 24 h after administration. However, administration of IOMNPs in SCI group slightly enhanced the pathological changes in the CNS after 24 h but not 4 h after trauma. Cerebrolysin treatment markedly attenuated IOMNP-induced aggravation of SCI-induced cord pathology and induced significant neuroprotection. These observations are the first to show that IOMNPs are safe for the CNS and cerebrolysin treatment prevented CNS pathology following a combination of trauma and IOMNP injection. This indicated that cerebrolysin might be used as adjunct therapy during IOMNP administration in disease conditions, not reported earlier. © 2017 Elsevier Inc.